Article 10 of ECtHR (Freedom of Expression) and the Limitations in the Light of the Case of Independent Newspapers (Ireland) Limited v. Ireland ECtHR 15.06.2017 (Final on 15.09.2017), Başvuru No: 28199 / 15 - Tok, Mehmet Can (Seçkin Yayıncılık, 2018)
Independent Newspaper Limited was publishing a newpaper. That newspaper had published story about a minister and a public relations consultant claiming that the two had a relationship and abused their positions because of that relationship. The photographs that were used in the story were altered. In the lawsuit against the company, the court awarded EUR 1,872,000 in the appeal, the award was reduced to EUR 1,250,000. The ECtHR found that the awawrd disproportionate and unreasonable. The Court stated that the system was not able to prevent such awards; there was a breach of Article 10.

Independent Newspaper Limited gazete yayımcısı bir şirkettir. Bu şirketin yayımladığı gazetede, bir bakan ve halkla ilişkiler danışmanı arasında bir ilişki olduğu ve sonucunda yolsuzluk yapıldığına dair haberler yayınlandı. Bu haberlerde kullanılan fotoğrafların ise üzerinde oynanmıştı. Şirkete karşı açılan davanın sonucunda EUR 1,872,000 tutarında tazminata hükmedildi. Temyiz sonucunda ise bu tazminat EUR 1,250,000’ye indirildi. AİHM ise bu tazminatı çok ağır ve olayla bağdaşmaz bulmuştur. Mahkeme sistemin bu çeşit tazminatları önlemek için yetersiz olduğunu ve dolayısıyla Madde 10’un ihlal edildiğini söylemiştir.
AİHS Madde 10 (İfade Özgürlüğü) ve Independent Newspapers (İrlanda) Limited v. İrlanda Kararı Işığında Bu Özgürlüğün Sınırlamaları AİHM Kt.: 15.06.2017 (Sonuç 15.09.2017), Başvuru No: 28199 / 15
Keywords: Art. 10 ECtHR; Freedom of Expression; Disproportionate Awards; Media; AİHS m. 10; İfade özgürlüğü; İfade özgürlüğünün sınırları; Orantısız tazminat; Basın